Study of quality of life and prognostic factors of patients with refractory epilepsy of Essaluds Miguel Grau Hospital, Lima – Peru - Pérez Galdós, Proel (2010)
Introduction: Quality of life is a subjective concept, and there are some questionnaires designed to determine it as accurately as possible, from the patients point of view. Objectives: To determine quality of life in patients with refractory epilepsy using the Quality-Of-Life in Epilepsy Inventory (QOLIE 31). Material and method: Thirty-five patients from the outpatient neurology clinic were selected in a descriptive and observational study, the QOLIE-31 was administered to them for self-use, and results were compared with socio-demographic and clinical data. Results: 68.6% were male, the mean age: 45.9 years, the average age of onset was: 16.1 years, the average time of disease was: 29.8 years, representing 60 TCG crisis %. An average low quality of life (= 60 points) in the domains: Effects of antiepileptic drugs (AEDs) 44.7, 56.8 cognitive functions and quality of life overall rating 57.1, being the overall score: 58.6 points. Conclusions: Results of the trial show low average values. The items with the lowest scores were follows: effects of antiepileptic drugs and cognitive function disorders, the latter being significantly affected by the use of many different antiepileptic drugs.